2011
DOI: 10.1002/ijc.25768
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA miR‐196a controls melanoma‐associated genes by regulating HOX‐C8 expression

Abstract: Resulting from a screening for microRNAs differentially regulated in melanocytes and melanoma cells, we found expression of miR-196a to be significantly down-regulated in malignant melanoma cell lines and tissue samples. As it was stated before that miR-196a might negatively regulate expression of the transcription factor HOX-C8, we analyzed HOX-C8 levels in NHEMs and melanoma cells and found a strong up-regulation of HOX-C8 expression in malignant melanoma cell lines and tissue samples compared with melanocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 48 publications
(58 reference statements)
5
76
0
1
Order By: Relevance
“…compiling data from several groups has enabled the coupling of differential miRNA expression in MM to specific target protein modulation and critically downstream functional consequence for disease (16)(17)(18)(19)(20)(21)(22)(23)(24). Such studies represent an emerging area of research, indeed, the prevalence of mirnas in the human transcriptome continues to expand as deep-sequencing technologies improve, with current estimates identifying ~9,000 small non-coding rnas, ~1,100 of which are potentially functional mirna transcripts (5).…”
Section: Long Non-coding Rnas Drive Metastatic Progression In Melanommentioning
confidence: 99%
“…compiling data from several groups has enabled the coupling of differential miRNA expression in MM to specific target protein modulation and critically downstream functional consequence for disease (16)(17)(18)(19)(20)(21)(22)(23)(24). Such studies represent an emerging area of research, indeed, the prevalence of mirnas in the human transcriptome continues to expand as deep-sequencing technologies improve, with current estimates identifying ~9,000 small non-coding rnas, ~1,100 of which are potentially functional mirna transcripts (5).…”
Section: Long Non-coding Rnas Drive Metastatic Progression In Melanommentioning
confidence: 99%
“…Notably, the micropthalmia-associated transcription factor (MITF), which is important for melanocyte development and function, is needed for high TRPM1 expression 31 , and thus, MITF contributes to miR-211 expression, suggesting that the tumor-suppressor activities of MITF may at least be partially executed through miR-211's tumor suppressing effect. MiR-196a is another documented tumor suppressor in melanoma by Dr.Bosserhoff's group 33,34 . First, they found that miR-196a was significantly down-regulated in malignant melanoma cell lines and tissue samples when screening differential miRNAs.…”
Section: Tumor Suppressor Mirnas In Melanomamentioning
confidence: 99%
“…Re-expressing miR-196a in vitro can dramatically reduce the invasive behavior of melanoma cells, which is partially believed to account for the negative regulating expression of the transcription factor HOX-C8, which is a member belonging to the homeobox genes family. By investigating a potential "miR-196a → HOX-C8 → target gene" model, they further identified cadherin-11, calponin-1, and osteopontin as the downstream targets of miR196a 34 . Additionally, they elucidated that down-regulated miR-196a in melanoma cells leads to enhanced HOX-B7 mRNA and protein levels, another member of the homeobox genes family, which subsequently raise Ets-1 activity, another transcription factor, by inducing basic fibroblast growth factor (bFGF).…”
Section: Tumor Suppressor Mirnas In Melanomamentioning
confidence: 99%
“…For example, MIR196 can repress several transcription factors and play a regulatory role in melanoma and acute leukemia. 67,68 Indeed, a number of genetic polymorphisms in the precursor or mature MIR196 have been © 2012 Landes Bioscience.…”
mentioning
confidence: 99%